Linear and nonlinear aeroelastic analyses of a typical airfoil section with control surface freeplay. - Eulo Antonio Balvedi Junior (2010)
This work presents an extensive analysis on the linear and nonlinear behavior of three degrees of freedom typical airfoil section oscillating in a bidimensional incompressible flow. The nonlinearity is introduced by means of control surface freeplay. The theoretical modeling of the aeroelastic system is reviewed from structural and aerodynamic standpoint. Two methodologies are used for generalized unsteady aerodynamic loads calculation: one developed by Theodorsen in frequency domain and other developed by Peters completely in time domain. Comparisons among the main flutter solution techniques available in literature are presented and discussed. These analyses provide guidance for the subsequent nonlinear analysis. On the nonlinear field, the limit cycle behavior is demonstrated through bifurcation diagrams, obtained via numerical simulations in time domain and harmonic linearizations in frequency domain. Moreover, the effects of aerodynamic loads selection are also discussed.